The impact of financial literacy on financial preparedness for retirement among formally employed individuals in Zimbabwe - Towo, Tendai; Jonasi, Knowledge (Annals of Management and Organization Research, 2024)
Purpose: Changes in global retirement systems have necessitated greater personal responsibility for making retirement financial decisions. The main purpose of this study is to evaluate the effect of financial literacy on the financial preparedness for retirement among the formally employed in Zimbabwe. Research Methodology: The study adopted a positivist philosophy and an explanatory research design. Questionnaires were used to collect data from a target population of employees in Bindura, Zimbabwe. The final sample consisted of 384 participants. The independent variable, financial literacy, was measured using knowledge of financial instruments and computational capabilities of retirement benefits. Data were analyzed by multiple regression analysis using SPSS version 25. Results: The findings show a statistically significant relationship between knowledge of financial instruments and financial preparedness for retirement at the 5% significance level. The computational capabilities of retirement benefits are found to have no effect on financial preparedness for retirement. Limitations: Other factors that affect financial preparedness, such as demographics and financial factors, were not included in the model. Contribution: This study addresses retirement preparedness, which is one of the least-researched areas of personal finance in Zimbabwe. Therefore, the results are useful for policymakers to enhance the framework of retirement financial literacy.